Comparison of breast density assessments according to BI-RADS 4th and 5th editions and experience level. (July 2020) - Gemici, Aysegul Akdogan; Bayram, Ersoy; Hocaoglu, Elif; Inci, Ercan
Background: Breast density is an important variable that can change the sensitivity of mammography. It can be analyzed with using the 4th and 5th editions of the Breast Imaging and Reporting Data System (BI-RADS) recommendations from the American College of Radiology (ACR). Purpose: To define the intra- and inter-reader agreement levels of breast density assignments performed by readers with different experience levels using two versions of BI-RADS. Material and Methods: The breast density assessments of 330 women were conducted by two readers with different levels of experience (one breast radiologist and one resident). Each reader independently defined the breast density four times—twice using the 4th edition and twice using the 5th edition. Assessments were analyzed on four- and two-category scales. Results: The intra-reader agreement of the breast radiologist for the 4th and 5th editions of BI-RADS was almost perfect (k = 0.90 and k = 0.87, respectively.) The resident had similar results (k = 0.88 and k = 0.87, respectively). The agreement between the breast radiologist and resident for the 4th and 5th edition of BI-RADS was substantial (k = 0.70 and k = 0.63, respectively). There was a statistically significant difference with the two-category scale analysis between the dense and non-dense for both readers and versions of BI-RADS (McNemar's test, P  < 0.001). Conclusion: Although there were high intra- and inter-reader agreement levels when using both versions, the percentage of women having dense breasts increased when using the 5th edition, and the difference was statistically significant. There were no differences found with regard to the readers' level of experience in all analyses.